Przejawy reprodukcji kapitału kulturowego na przykładzie młodzieży gimnazjalnej społeczności lokalnych Podkarpacia = Indications of the Reproduction of Cultural Capital Illustrated on the Example of Middle School Students from Podkarpacie Province - Broszkiewicz, Wojciech (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Theoretical context of the presented research on the determinants of cultural capital of young people comprises Bourdieu`s Reproduction Theory, the concepts of information society (macrosocial level) and peripheral communities (mesosocial level). 1002 middle school students participated in the research, and the research tool also included the set of questions concerning young people`s parents. Stratified sampling and group sampling were applied.
Keywords: kapitał kulturowy; szkolnictwo ponadpodstawowe; gimnazjaliści; województwo podkarpackie